A rare cause of idiopathic right outflow tract premature ventricular contraction: Type‐4 renal tubular acidosis. Issue 6 (11th February 2022) - Atici, Adem; Tatlisu, Mustafa Adem; Baycan, Omer Faruk; Yılmaz, Yusuf; Caliskan, Mustafa
Abstract: The premature ventricular contractions (PVCs) have usually good prognosis in patients without structural heart disease. In case of left ventricular ejection fraction depression or symptoms, antiarrhythmic drugs or cardiac ablations could be an option for management. We present a case of a patient with high burden of PVC admitted for cardiac ablation. Preoperative assessment revealed hyperkalemia and metabolic acidosis which ended up with type‐4 renal tubular acidosis (RTA). Its rare cause and management may draw attention to the possibility of type ‐4 RTA as the cause of the PVC, and hyperkalemia.